The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.jmedchem.0c00227
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Structure–Activity Relationship Study of (Z)-5-Methylenethiazolidin-4-one Derivatives as Potent and Selective Pan-phosphatidylinositol 5-Phosphate 4-Kinase Inhibitors

Abstract: Due to their role in many important signaling pathways, phosphatidylinositol 5-phosphate 4-kinases (PI5P4Ks) are attractive targets for the development of experimental therapeutics for cancer, metabolic, and immunological disorders. Recent efforts to develop small molecule inhibitors for these lipid kinases resulted in compounds with low- to sub-micromolar potencies. Here, we report the identification of CVM-05-002 using a high-throughput screen of PI5P4Kα against our in-house kinase inhibitor library. CVM-05-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…While this paper was under review, two new classes of chemical probes targeting PI5P4K were reported (62)(63)(64). Although these inhibitors appear to have weaker affinities than CC260 in vitro, one of them can react covalently with a free cysteine adjacent to the lipid kinase's active site, which should enhance its effectiveness and selectivity.…”
Section: Discussionmentioning
confidence: 99%
“…While this paper was under review, two new classes of chemical probes targeting PI5P4K were reported (62)(63)(64). Although these inhibitors appear to have weaker affinities than CC260 in vitro, one of them can react covalently with a free cysteine adjacent to the lipid kinase's active site, which should enhance its effectiveness and selectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Of the compounds retested, 580 were confirmed to be active in this dose−response qHTS assay, representing a 43% confirmation rate. Importantly, almost all of these compounds were inactive in previous NCATS screens against PI4K2A and PI5P4Ka which also used the ADP-Glo format, 13,14 suggesting that they are selective against other lipid kinases and not assay artifacts.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…In fact, efforts have been made to identify and characterize pan inhibitors [33,34] as well as isoform specific inhibitors of PI5P4Ks [75,76], and over the years, there have been reports of more potent and selective small molecule inhibitors [60,[77][78][79], strengthening the evidence for efficient druggability of the PI5P4Ks. Recently in an attempt to identify drugs that are selectively lethal to cancer cells but not to normal cells, a novel compound, a131, was identified and interestingly, the group discovered that the target of the a131 compound is indeed the PI5P4Ks and it selectively regulated the cell cycle entry of Ras-activated cancer cells resulting in their death through mitotic catastrophe, while causing reversible growth arrest in normal cells [77].…”
Section: Targeting Pi5p4ks With Small Molecule Inhibitorsmentioning
confidence: 99%
“…In a follow-up study by the same group, they sought to find reversible inhibitors of PI5P4Ks so that issues associated with acquired resistance of tumor cells could be avoided. Among a library of approximately 6000 kinase inhibitors, they identified a potent inhibitor and further developed a pan-PI5P4K inhibitor with better selectivity [78]. Most recently, a noncovalent dual PI5P4Ka/b inhibitor, CC260, was identified using a high-throughput screen among 5759 small molecules.…”
Section: Targeting Pi5p4ks With Small Molecule Inhibitorsmentioning
confidence: 99%